2016
DOI: 10.1007/s10549-016-3852-6
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation assessment in breast carcinomas using digital image analysis based on virtual Ki67/cytokeratin double staining

Abstract: Manual estimation of Ki67 Proliferation Index (PI) in breast carcinoma classification is labor intensive and prone to intra- and interobserver variation. Standard Digital Image Analysis (DIA) has limitations due to issues with tumor cell identification. Recently, a computer algorithm, DIA based on Virtual Double Staining (VDS), segmenting Ki67-positive and -negative tumor cells using digitally fused parallel cytokeratin (CK) and Ki67-stained slides has been introduced. In this study, we compare VDS with manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
(18 reference statements)
1
29
0
Order By: Relevance
“…The scoring of cells as either Ki67‐positive or Ki67‐negative was performed with the Visiopharm Ki67 Breast Cancer APP, whereas the scoring of PHH3 was performed with a PHH3 APP that was custom‐made for this project. This system has previously been shown to have excellent reproducibility and correlation with manual assessments …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoring of cells as either Ki67‐positive or Ki67‐negative was performed with the Visiopharm Ki67 Breast Cancer APP, whereas the scoring of PHH3 was performed with a PHH3 APP that was custom‐made for this project. This system has previously been shown to have excellent reproducibility and correlation with manual assessments …”
Section: Methodsmentioning
confidence: 99%
“…This system has previously been shown to have excellent reproducibility and correlation with manual assessments. 16,17,33,34 We evaluated the percentage of cells stained by Ki67 and PHH3 in the following regions: (i) the tumour's invasive margin; (ii) the highest-intensity hot spots; and (iii) across the full tumour section.…”
Section: Full Sections Full Sectionsmentioning
confidence: 99%
“…Medical image analysis methods can enable objective stain quality control by reproducible quantification of staining characteristics . These techniques for Ki67 quantification have been applied in tissues but never as surrogate of IHC staining quality in cell lines . Extracting features such as Ki67 PI and stain intensity of the cell nuclei within the cell line may be used to serve as a more robust and objective assessment of the stain quality .…”
mentioning
confidence: 99%
“…Visiopharm (Hoersholm, Denmark) Virtual Double Staining techniques is using a pancytokeratin-stained tissue section, which is aligned to the IHC-stained biomarker of interest and enables automated detection of tumor regions (Fig 2). [91][92][93] The abovementioned commercial platforms operate on input from a WSI scanner, whereas the Aperio Digital Pathology (Leica Biosystems, Nussloch, Germany) platform operates by integrating a digital microscope with the image software. The Aperio Digital Pathology usersupervised platform has been compared with the automated Definiens Tissue Studio platform for classification of ER and PR IHC positivity.…”
Section: Existing Digital Image Analysis Methodsmentioning
confidence: 99%
“…DIA has shown excellent reproducibility, although limited to subsets with individual biomarkers or smaller cohorts. 93,[95][96][97] Hartman et al have recently shown the advantages in congruence to gene expression assays and the prognostic power of digital image analysis compared with current manual methods of biomarker assessments. 91 Automated image analysis has been applied to analyze several biomarkers, including HER2 expression, holding promise to reduce the need for additional ISH analysis in HER2 equivocal cases 95,98 and significantly reducing inter-and intraobserver variability.…”
Section: Existing Digital Image Analysis Methodsmentioning
confidence: 99%